Differential gene expression in East African highland bananas (Musa spp.): interactions between nonpathogenic Fusarium V5w2 and Radopholus similis - Paparu, P.; Dubois, T.; Coyne, Danny L.; Viljoen, Altus (Elsevier, 2013)
Endophytic non-pathogenic Fusarium oxysporum isolates are known to control Radopholus similis through induced resistance. Using complementary (c)DNA-amplified fragment length polymorphism (cDNA-AFLP), we identified genes induced in nematode-susceptible and -tolerant bananas following colonization by non-pathogenic endophytic F. oxysporum isolate V5w2. Quantitative real-time polymerase chain reactions (qRT-PCR) were then used to analyze expression profiles of selected genes. Accumulated gene transcripts included those involved in signal transduction, cell wall strengthening, Jasmonic acid (JA) pathway and transport of defense molecules. Endophyte colonization primed the expression of b-1,3-glucan synthase and Coronatine insensitive 1 (COI1) in the susceptible cultivar, and that of COI1 and Lipoxygenase (LOX) in the tolerant.We isolate and identify for the first time genes involved in the interaction between endophytic non-pathogenic F. oxysporum and banana.